STUDI GEJALA FONEMIS ANTARA BAHASA MELAYU RIAU DIALEK KAMPAR DAN BAHASA INDONESIA (Sebuah Pendekatan Historis) - Martius Martius (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Symptoms phonemic language is a symptom caused by the absorption of a word from one language to the absorber or the decline of a language from one generation to the next. The process of obtaining the absorption or reduction led to changes in the form of words or phonemic symptoms. This study will describe symptoms that exist between BMRDK phonemic and BI. Having analyzed using the match to equalize relations techniques appeal (HBS) and comparative relations techniques to distinguish (HBB), the obtained conclusion that there is some form of phonemic symptoms. Symptoms are: (1) Symptoms addition of phonemes, which consists of the addition of phonemes at the beginning of the word (protesis), the addition of phonemes in the word (epentesis), and addition of phonemes at the end of words (paragog), (2) Changes in phonemes, which includes ponem changes in initial position word, change word phonemes at the center position, and change the word phoneme in final position, (3) combination (merger), the phoneme / g, R, u, and w / in KBMRDK merger into the phoneme / r / the KBI, (4) Cleavage (Spilit), the phoneme /? / in KBMRDK split into phonemes / p / and / t / in BI.